Robust Voltage Sag Compensation Using a Matrix Converter DVR and Sliding Mode Control Technique - Soomro, Abdul Hameed; Laghari, Imtiaz Ali; Kaloi, Ghulam Sarwar; Sohoo, Zainab; Khatoon, Safina (Sir Syed University research journal of engineering and technology, 2024)
Problems related to voltage sags in distribution systems of electrical power add a number of challenges to the efficient performance of sensitive loads, hence the need for mitigation. The Dynamic Voltage Restorer (DVR) is a specialized device designed to counteract both low and high levels of voltage sags by being connected in series with the load. This paper introduces an application of a three-phase Matrix Converter for DVRs, which is capable of direct AC-AC power conversion without the need for an energy storage component. Motivated by the need for efficient and responsive voltage sag correction, a sliding mode controller with a Proportional-Integral sliding surface and hysteresis control is proposed. The traditional methods such as the real-coded genetic algorithm were considered but, these methods typically involve extended convergence times to optimize the PI gains of the Sliding Mode Control (SMC). To this effect, the Ant Colony Optimization (ACO) technique was used and generated the best values of PI gains of 6.87688 and 0.850851. The effectiveness of the SMC was tested under fault conditions and varying load scenarios using MATLAB simulation software, demonstrating satisfactory performance and stabilization at the onset of voltage sags. The DVR's performance, empowered by the Matrix Converter with the SMC framework, has been thoroughly analyzed, and the THD% was further scrutinized using the Fast Fourier Transform (FFT). This research confirms the Matrix Converter integrated with SMC as a robust solution for dynamic voltage restoration, providing a promising avenue for enhancing power quality in modern electrical distribution networks.